Peran Mikroorganisme sebagai Kunci Pertanian Berkelanjutan : Kajian Literaur - Septin Melindra Gulo; Natalia Kristiani Lase (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Microorganisms are highly beneficial in sustainable agriculture as they are key components of the soil ecosystem and participate in various processes that enhance soil fertility, improve crop quality, and reduce reliance on synthetic chemicals. This study employs a meta-analysis or literature review method to examine previous research on the role of microorganisms in agriculture, specifically on how microorganisms play a critical role in sustainable farming. Most available studies rely on qualitative data or case studies, limiting the ability to conduct more in-depth quantitative analysis. The results indicate that waste processing into organic compost fertilizer is crucial. Applying organic farming methods improves crop quality while maintaining ecosystem balance.